Managing Harlequin Syndrome in VA-ECMO – do not forget the right ventricle. (July 2022) - Wilson, James; Fisher, Richard; Caetano, Francisca; Soliman-Aboumarie, Hatem; Patel, Brijesh; Ledot, Stephane; Price, Susanna; Vandenbriele, Christophe
Harlequin Syndrome (also known as North-South Syndrome) is a complication of veno-arterial extracorporeal membrane oxygenation (V-A ECMO) that can occur when left ventricular function starts to recover. While most commonly due to continued impaired gas exchange in the lungs, we present a case caused by right ventricular dysfunction, successfully managed by conversion of the ECMO circuit to a veno-veno-arterial (VV-A) configuration.